(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
In my study, the appearance, existence and operational aspects of robots in educational processes are discussed. Robots can be a source of danger, but at the same time, effective solutions are present in our lives and we are involved in continuous improvement. No doubt to understand that the need for electronic communication tools, algorithms and sensors, knowledge of artificial intelligence, and robotics becoming self-evident in our lives, and the IT education will need relaunch. In this way, the presence of educational robots is a leading trend for teachers and students. The purpose of this study is to provide an insight into educational foundation of robotics, its roles and opportunities in education. Technical and digital education is becoming more dynamic at all levels of training, the competences of logical and algorithmic thinking, creativity, collaborative abstraction skills and problemsolving can be developed with the help of these digital tools named educational robots.